A graphene-modified high thermal conductivity plastic and preparation method thereof
By using graphene modified high thermal conductivity plastic as the shell material of the power battery pack, the existing materials are solved in the difficult problem between thermal runaway protection and lightweight design, and the comprehensive improvement of high thermal conductivity, heat dissipation and safety are achieved.
Patent Information
- Application Number
- CN202410733313.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-07
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-06-07
AI Technical Summary
The shell materials of existing power battery packs are difficult to take into account between thermal runaway protection and lightweight design, and the thermal conductivity is poor, which affects the use temperature performance.
Graphene-modified high thermal conductivity plastics are used as shell material, and materials with good thermal conductivity, heat dissipation, mechanical properties, flame retardancy and electrical breakdown insulation safety are prepared by combining nylon matrix resin, graphene-modified polyaniline resin, surface-modified aramid fibers and nano high thermal insulation fillers.
It realizes the balance of thermal runaway protection and lightweight design of the power battery pack, improves the range of kilometers per single charge, and improves the overall operating temperature performance.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of thermally conductive insulating plastics, and in particular to a graphene-modified high thermal conductive plastic and a preparation method thereof. Background Art
[0002] New energy vehicles are one of the most popular means of transportation at present. The main contradictions restricting their development are: the thermal runaway safety protection performance of the power battery pack and the mileage of the single charge of the power battery pack of new energy vehicles. The thermal runaway safety protection performance of the power battery pack is the most important assessment indicator to ensure the life safety of the driver. The mileage of a single charge is a reflection of the driving convenience and performance of new energy vehicles, and is also one of the factors that restrict consumers from choosing new energy vehicles.
[0003] At present, the shell material of the power battery pack is mainly aluminum alloy shell. In order to ensure the overall thermal runaway safety of the power battery pack, car companies usually pad the inside of the aluminum alloy shell with insulating fireproof materials. The most popular insulating fireproof material in the market is mica composite material. Although the shell structure of the power battery pack with the above-mentioned aluminum alloy shell / insulating fireproof material has a good thermal runaway protection effect, the overall weight is not conducive to the lightweight design of the power battery pack, affecting the improvement of the mileage of a single charge, and the power battery pack will release heat during use. The shell of the power battery pack with the above-mentioned aluminum alloy shell / insulating fireproof material has poor thermal conductivity, and heat is relatively easy to accumulate, affecting the overall use temperature performance of the power battery pack. To this end, the present application provides a graphene-modified high thermal conductivity and high insulation plastic as a shell material for a power battery pack. Summary of the invention
[0004] In order to solve the above technical problems, the present application provides a graphene-modified high thermal conductivity plastic and a preparation method thereof.
[0005] The present application provides a graphene-modified high thermal conductivity plastic, which is realized by the following technical solutions:
[0006] A graphene-modified high thermal conductivity plastic is mainly prepared from nylon matrix resin, graphene-modified polyaniline resin, surface-modified aramid fiber, and nanometer high thermal conductivity insulation filler;
[0007] The mass of the surface-modified aramid fiber accounts for 5-10% of the total mass of the high thermal conductivity plastic;
[0008] The surface-modified aramid fiber comprises an aramid fiber and a high thermal conductivity metal oxide film fixedly connected to the aramid fiber;
[0009] The nanometer high thermal conductivity insulating filler is at least one of aluminum oxide, aluminum nitride, boron nitride and zirconium nitride;
[0010] The mass of the nano high thermal conductivity insulating filler accounts for 15-30% of the total mass of the high thermal conductivity plastic;
[0011] The mass of the graphene-modified polyaniline resin accounts for 10-20% of the total mass of the high thermal conductivity plastic;
[0012] The graphene-modified polyaniline resin contains 4-8wt% of hydroxylated graphene, 5-10wt% of nano-carbon fiber, and 1-5wt% of spherical alumina powder with hydrophilic surface treatment; the nano-carbon fiber is treated with low-temperature plasma;
[0013] The nylon matrix resin is at least one of PA6, PA66, PA56, PA612, and PA1212.
[0014] The high thermal conductivity plastic prepared in the present application not only has good thermal conductivity and heat dissipation, but also has good mechanical properties, flame retardancy and anti-electrical breakdown insulation safety, and is suitable for the field of shell materials for thermal runaway protection of power batteries.
[0015] Preferably, the aramid fiber has a length of 0.5-5.0 mm; and an aluminum oxide film layer is formed on the surface of the aramid fiber by a sol-gel method.
[0016] By adopting the above technical scheme, the aluminum oxide film layer can improve the high thermal performance of the surface-modified aramid fiber without affecting the overall anti-electrical breakdown insulation performance. The high thermal conductivity plastic prepared by the above aluminum oxide film layer / surface-modified aramid fiber not only has excellent thermal conductivity and anti-electrical breakdown insulation performance, but also has good flame retardancy, wear resistance and mechanical properties.
[0017] Preferably, the nano high thermal conductive insulating filler is composed of spherical alumina, spherical aluminum nitride, and boron nitride nanosheets in a mass ratio of (3-6):(3-6):(0.5-2).
[0018] Preferably, the nano high thermal conductive insulating filler is composed of spherical alumina, spherical aluminum nitride, and boron nitride nanosheets in a mass ratio of 5:4:1.
[0019] By adopting the above technical solution, the prepared high thermal conductivity plastic is endowed with excellent thermal conductivity and electrical breakdown resistance insulation performance, and also has good flame retardancy, wear resistance, weather resistance and mechanical properties.
[0020] Preferably, the spherical alumina is surface-doped graphene-modified spherical alumina; the surface-doped graphene-modified spherical alumina comprises spherical alumina with an average particle size of 1-40 microns and 3D graphene fixed to the spherical alumina by sintering of nanosilver clusters; the average particle size of the boron nitride nanosheets is 200-600nm.
[0021] Preferably, the spherical aluminum nitride is surface-doped graphene-modified spherical aluminum nitride; the surface-doped graphene-modified spherical aluminum nitride includes spherical aluminum nitride with an average particle size of 1-40 microns and 3D graphene fixed to the spherical aluminum nitride by sintering of nanosilver clusters.
[0022] By adopting the above technical solution, the overall thermal conductivity is further improved while still having good anti-electrical breakdown insulation performance.
[0023] Preferably, the mass of the surface-modified aramid fiber accounts for 6-8% of the total mass of the high thermal conductivity plastic; the mass of the nano high thermal conductivity insulating filler accounts for 24-28% of the total mass of the high thermal conductivity plastic; the mass of the graphene-modified polyaniline resin accounts for 15-18% of the total mass of the high thermal conductivity plastic; and the nylon matrix resin is composed of PA66 and PA612 in a mass ratio of (6-8):(2-4).
[0024] Preferably, the graphene-modified polyaniline resin contains 5-6wt% of hydroxylated graphene, 6-8wt% of nano-carbon fibers, and 3-4wt% of spherical alumina powder with a surface hydrophilic treatment; the length of the nano-carbon fibers is 5-50um, and the diameter of the nano-carbon fibers is 150-200nm; the spherical alumina powder with a surface hydrophilic treatment is obtained by surface hydrophilic treatment with a coupling agent, and the average particle size of the spherical alumina powder is 50-500nm; the coupling agent used for the surface hydrophilic modification of the spherical alumina powder is composed of γ-methacryloxypropylmethyldimethoxysilane and titanate coupling agent KR138S in a mass ratio of (80-85):(15-20).
[0025] By optimizing the ratio of nylon matrix resin, graphene-modified polyaniline resin, surface-modified aramid fiber, and nano-high thermal conductivity insulating filler, a finished graphene-modified high thermal conductivity plastic with high thermal conductivity and high insulation as well as good flame retardancy, weather resistance, hydrolysis stability, and mechanical strength can be prepared, thereby expanding its overall scope of use.
[0026] Preferably, the preparation method of graphene-modified polyaniline resin is as follows:
[0027] Step 1, preparation of hydroxylated graphene; low-temperature plasma treatment of nano-carbon fibers; surface hydrophilic treatment of spherical alumina powder;
[0028] Step 2, dissolving aniline in a 1-2 mol / L hydrochloric acid solution and mixing well to obtain an acidic polyaniline aqueous solution, wherein the mass ratio of the aniline to the hydrochloric acid is 1:(8-10);
[0029] At the same time, the hydroxylated graphene in step 1, the spherical alumina powder with hydrophilic surface treatment, and the nano-carbon fiber treated with low-temperature plasma are added into deionized water, with a solid-liquid ratio of 1:(19-24), and ultrasonically dispersed for 3-6 hours to obtain an aqueous dispersion of a high thermal conductivity powder;
[0030] Step 3, at a speed of 300-500 rpm / min, the aqueous dispersion of the high thermal conductivity powder is added dropwise to the acidic polyaniline aqueous solution at a dropping speed of 1-2 drops / s, and after the addition is completed, stirring is continued at a speed of 300-500 rpm / min for 6-8 hours to obtain a milky white mixed solution;
[0031] Step 4, cooling to 0-4°C, adding 0.1-0.5 wt% of initiator to the milky white mixed solution at 160-240 rpm / min, stirring for 10-12 hours, and standing at 0-4°C for 20-24 hours to allow aniline to fully polymerize to obtain a solution containing a black-green precipitate;
[0032] Step 5: The solution containing the black-green precipitate is subjected to vacuum filtration to obtain the black-green precipitate, and the black-green precipitate is washed alternately with deionized water and ethanol for at least three times, and finally vacuum dried to obtain graphene-modified polyaniline resin particles.
[0033] The preparation method of the graphene-modified polyaniline resin particles in the present application is relatively simple and convenient for mass production.
[0034] The present application provides a method for preparing a graphene-modified high thermal conductivity plastic, which is achieved by the following scheme:
[0035] A method for preparing a graphene-modified high thermal conductivity plastic comprises the following steps:
[0036] Step 1. Preparation of graphene-modified polyaniline resin and surface-modified aramid fiber; simultaneously, surface treatment of nano-high thermal conductive insulating filler is performed, and nano-high thermal conductive insulating filler and coupling agent are dry-kneaded at a mass ratio of 100:(3-8) for at least 0.5h;
[0037] Step 2. The nylon matrix resin is dissolved in an organic solvent to form a nylon solution, wherein the mass of the organic solvent is 8-12 times the mass of the nylon matrix resin, and the graphene-modified polyaniline resin, the surface-modified aramid fiber, and the surface-treated nano-high thermal conductive insulating filler in step 1 are added to the nylon solution. After being fully dissolved, the mixture is stirred at 200-400 rpm / min for 10-15 min, ultrasonically dispersed for 2-4 h, and the organic solvent is removed by distillation under reduced pressure to obtain a solid mixed resin;
[0038] Step 3. The solid mixed resin in step 3 is crushed and vacuum dried to obtain a mixed resin powder;
[0039] Step 4. Extrude, granulate and dry the mixed resin powder in step 3 to obtain a high thermal conductivity and high insulation plastic masterbatch;
[0040] Step 5. Using the high thermal conductivity and high insulation plastic masterbatch in step 4 for extrusion, melting, and injection molding to obtain a semi-finished plastic;
[0041] Step 6. Heat-treating the semi-finished plastic in step 5 can produce a finished graphene-modified high thermal conductivity plastic.
[0042] The preparation method provided in this application has relatively low requirements for production equipment, relatively small investment cost for production equipment, relatively low difficulty in implementation, and the raw materials can be outsourced for processing and customization, which facilitates industrial production and reduces overall production costs.
[0043] Preferably, in step six, the semi-finished plastic in step five is heat-treated, the temperature is increased to 60-65°C at 0.5-3°C / min and kept warm for 10-30min, then the temperature is increased to 90-125°C at 2-4°C / min and kept warm for 30-45min, the temperature is decreased to 40-45°C at 0.2-0.8°C / min, the furnace is opened and naturally cooled to room temperature, and a finished graphene-modified high thermal conductivity plastic can be obtained.
[0044] By adopting the above technical scheme, heat treatment can effectively eliminate the internal stress of the finished graphene-modified high thermal conductivity plastic, thereby improving the overall mechanical properties and heat resistance; and can improve the distribution uniformity of graphene-modified polyaniline resin, surface-modified aramid fiber, and nano high thermal conductivity insulating filler in the finished graphene-modified high thermal conductivity plastic, thereby improving the thermal conductivity and electrical breakdown resistance of the finished graphene-modified high thermal conductivity plastic.
[0045] In summary, this application has the following advantages:
[0046] 1. The high thermal conductivity plastic prepared in this application not only has good thermal conductivity and heat dissipation, but also has good mechanical properties, flame retardancy and anti-electrical breakdown insulation safety, and is suitable for the field of shell materials for thermal runaway protection of power batteries.
[0047] 2. In this application, graphene-modified polyaniline resin, surface-modified aramid fiber, and nano-high thermal conductivity insulating filler are used to construct a relatively dense three-dimensional network thermal conductive structure to effectively improve the overall thermal conductivity and heat dissipation while ensuring the overall anti-electrical breakdown insulation safety and flame retardant performance, as well as heat-resistant performance. It is an ideal shell material for thermal runaway protection of power batteries.
[0048] 3. The preparation method provided in this application has relatively low requirements for production equipment, the investment cost of production equipment is relatively small, the implementation difficulty is relatively low, and the raw materials can be outsourced for processing and customization, which facilitates industrial production and reduces overall production costs. DETAILED DESCRIPTION
[0049] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples and comparative examples.
[0050] Preparation Example
[0051] Preparation Example 1: Nano high thermal conductive insulating filler is composed of spherical alumina with an average particle size of 10 microns (customized by Zhejiang Yamei Nano Technology), spherical aluminum nitride with an average particle size of 40 microns (customized by Shanghai Chaowei Nano Technology), and boron nitride nanosheets with an average particle size of 200nm (customized by Zhejiang Yamei Nano Technology) in a mass ratio of 6:3:1.
[0052] The preparation method of nano high thermal conductive insulating filler is as follows: 60g of spherical alumina with an average particle size of 10 microns, 60g of spherical aluminum nitride with an average particle size of 40 microns, and 20g of boron nitride nanosheets with an average particle size of 200nm are weighed and placed in a high-speed reactor and mixed at a high speed of 600rpm / min for 30min; 140g of the obtained mixed filler is dry-kneaded with 9g of KH570 coupling agent and 1g of KR 138S titanate coupling agent for 30min to obtain nano high thermal conductive insulating filler.
[0053] The difference between Preparation Example 2 and Preparation Example 1 is that the nano high thermal conductive insulating filler is composed of spherical alumina with an average particle size of 10 microns, spherical aluminum nitride with an average particle size of 40 microns, and boron nitride nanosheets with an average particle size of 200 nm in a mass ratio of 5:4:1.
[0054] The difference between Preparation Example 3 and Preparation Example 1 is that the nano high thermal conductive insulating filler is composed of spherical alumina with an average particle size of 10 microns, spherical aluminum nitride with an average particle size of 40 microns, and boron nitride nanosheets with an average particle size of 200 nm in a mass ratio of 3:6.5:0.5.
[0055] The difference between Preparation Example 4 and Preparation Example 1 is that the nano high thermal conductive insulating filler is composed of spherical alumina with an average particle size of 10 microns, spherical aluminum nitride with an average particle size of 40 microns, and boron nitride nanosheets with an average particle size of 200 nm in a mass ratio of 1:1:1.
[0056] The difference between Preparation Example 5 and Preparation Example 1 is that the nano high thermal conductive insulating filler is composed of spherical alumina with an average particle size of 10 microns, spherical aluminum nitride with an average particle size of 40 microns, and boron nitride nanosheets with an average particle size of 200 nm in a mass ratio of 8:1.5:0.5.
[0057] The difference between Preparation Example 6 and Preparation Example 1 is that the nanometer high thermal conductive insulating filler is composed of spherical aluminum oxide with an average particle size of 10 microns and spherical aluminum nitride with an average particle size of 40 microns in a mass ratio of 1:1.
[0058] The difference between Preparation Example 7 and Preparation Example 1 is that the nanometer high thermal conductive insulating filler is composed of spherical aluminum oxide with an average particle size of 10 micrometers and boron nitride nanosheets with an average particle size of 200 nm in a mass ratio of 8:2.
[0059] The difference between Preparation Example 8 and Preparation Example 1 is that the nano high thermal conductive insulating filler is composed of spherical aluminum nitride with an average particle size of 40 microns and boron nitride nanosheets with an average particle size of 200 nm in a mass ratio of 8:2.
[0060] The difference between Preparation Example 9 and Preparation Example 2 is that the spherical aluminum nitride is surface-doped graphene-modified spherical aluminum nitride. The surface-doped graphene-modified spherical aluminum nitride includes spherical aluminum nitride with an average particle size of 40 microns and 3D graphene fixed to the spherical aluminum nitride by sintering nanosilver clusters.
[0061] The preparation method of surface-doped graphene-modified spherical aluminum nitride (customized by Zhejiang Rongtai Technology) is as follows:
[0062] Step 1: add 2.2 g of 2-ethyl-4-methylimidazole 2E4MI and 1.67 g of silver acetate AgAc to 530 g of dichloromethane at room temperature, and stir magnetically at 200 rpm for 120 min to obtain a clear and transparent Ag(2E4MI)2Ac complex solution;
[0063] Step 2: Add 5 g of 3D graphene TN3DPRGO (purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences) and 5 g of polyvinyl pyrrolidone to the prepared Ag(2E4MI)2Ac complex solution, perform ultrasonic dispersion for 6 h, ultrasonic frequency of 60 kHz, ultrasonic power of 800 W, add 50 g of spherical aluminum nitride with an average particle size of 40 μm (customized by Shanghai Chaowei Nano), and continue ultrasonic dispersion for 1 h to obtain a dispersion; the obtained dispersion is distilled under reduced pressure to remove dichloromethane to obtain a solid;
[0064] Step three, the obtained solid is subjected to high temperature sintering treatment, sintered at 215° C. for 4 hours to obtain a block solid, and the block solid is subjected to air flow pulverization treatment to obtain surface-doped graphene-modified spherical aluminum nitride with an average particle size of 40-45 μm.
[0065] The difference between Preparation Example 10 and Preparation Example 2 is that the spherical alumina is surface-doped graphene-modified spherical alumina. The surface-doped graphene-modified spherical alumina includes spherical alumina with an average particle size of 10 microns and 3D graphene fixed to the spherical alumina by sintering of nanosilver clusters.
[0066] The preparation method of surface-doped graphene-modified spherical alumina (customized by Zhejiang Rongtai Technology) is as follows:
[0067] Step 1: add 2.2 g of 2-ethyl-4-methylimidazole 2E4MI and 1.67 g of silver acetate AgAc to 530 g of dichloromethane at room temperature, and stir magnetically at 200 rpm for 120 min to obtain a clear and transparent Ag(2E4MI)2Ac complex solution;
[0068] Step 2: Add 5 g of 3D graphene TN3DPRGO (purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences) and 5 g of polyvinyl pyrrolidone to the prepared Ag(2E4MI)2Ac complex solution, perform ultrasonic dispersion for 6 hours, ultrasonic frequency of 60 kHz, ultrasonic power of 800 W, add 40 g of spherical alumina with an average particle size of 40 microns and an average particle size of 10 microns (customized by Zhejiang Yamei Nano Technology) after the ultrasonic treatment, and continue ultrasonic dispersion for 1 hour to obtain a dispersion; the obtained dispersion is distilled under reduced pressure to remove dichloromethane to obtain a solid;
[0069] Step three, the obtained solid is subjected to high temperature sintering treatment, sintered at 215° C. for 4 hours to obtain a block solid, and the block solid is subjected to air flow pulverization treatment to obtain surface-doped graphene-modified spherical alumina with an average particle size of 10-12 μm.
[0070] The difference between Preparation Example 11 and Preparation Example 1 is that the nano high thermal conductive insulating filler is composed of the surface-doped graphene-modified spherical alumina in Preparation Example 10, the surface-doped graphene-modified spherical aluminum nitride in Preparation Example 9, and boron nitride nanosheets with an average particle size of 200 nm in a mass ratio of 5:4:1.
[0071] Preparation Example 12: The surface-modified aramid fiber has a length of 4 mm and includes aramid F-12 monofilaments (each fiber has a diameter of 14 μm) and an aluminum oxide film layer fixedly connected to the aramid fiber. The aluminum oxide film layer is prepared by a sol-gel pulling method.
[0072] The preparation method of the surface modified aramid fiber is as follows:
[0073] S1, using an electronic balance to measure 40g of aluminum nitrate nonahydrate, putting it into a beaker, adding 60g of distilled water, stirring with a magnetic force and heating to 70°C until the aluminum nitrate is completely dissolved to obtain an aluminum nitrate aqueous solution with a concentration of 40wt%; at the same time, preparing a sodium carbonate aqueous solution with a concentration of 25wt%, dripping the prepared sodium carbonate aqueous solution with a concentration of 25wt% into the aluminum nitrate aqueous solution with a concentration of 40wt% at a uniform speed of 2 drops / s, adjusting the pH value of the solution to 5-5.2 and stirring for 120min, then dripping 25wt% sodium carbonate aqueous solution to adjust the pH value of the system to 5-5.2, and standing and aging for 24h to obtain an aluminum hydroxide sol with Tyndall effect;
[0074] S2, immerse the aramid F-12 monofilament in the aluminum hydroxide sol in step 1 for 30 seconds, then pull the aramid F-12 monofilament out of the aluminum hydroxide sol at a speed of 1 cm / min, and place it in a cool and ventilated place to dry. The obtained aramid F-12 monofilament is placed at 300°C for thermal decomposition for 45 minutes, and the aluminum hydroxide sol attached to the surface of the aramid F-12 monofilament is thermally decomposed to form an aluminum oxide film layer.
[0075] The difference between Preparation Example 13 and Preparation Example 12 is that: in S2 in the preparation method of surface-modified aramid fiber, the aramid F-12 monofilament is immersed in the aluminum hydroxide sol in step one for 20 seconds, and then the aramid F-12 monofilament is pulled out from the aluminum hydroxide sol at a speed of 2 cm / min and placed in a cool and ventilated place to dry. The obtained aramid F-12 monofilament is thermally decomposed at 300°C for 45 minutes, and the aluminum hydroxide sol attached to the surface of the aramid F-12 monofilament is thermally decomposed to form an aluminum oxide film layer.
[0076] The difference between Preparation Example 14 and Preparation Example 12 is that: in S2 in the preparation method of surface-modified aramid fiber, the aramid F-12 monofilament is immersed in the aluminum hydroxide sol in step one for 40 seconds, and then the aramid F-12 monofilament is pulled out from the aluminum hydroxide sol at a speed of 2 cm / min and placed in a cool and ventilated place to dry. The obtained aramid F-12 monofilament is thermally decomposed at 300°C for 45 minutes, and the aluminum hydroxide sol attached to the surface of the aramid F-12 monofilament is thermally decomposed to form an aluminum oxide film layer, which is cut into 4 mm.
[0077] The difference between Preparation Example 15 and Preparation Example 12 is that: in S2 in the preparation method of the surface-modified aramid fiber, the aramid F-12 monofilament is immersed in the aluminum hydroxide sol in step one for 60 seconds, and then the aramid F-12 monofilament is pulled out from the aluminum hydroxide sol at a speed of 3 cm / min and placed in a cool and ventilated place to dry. The obtained aramid F-12 monofilament is thermally decomposed at 300°C for 45 minutes, and the aluminum hydroxide sol attached to the surface of the aramid F-12 monofilament is thermally decomposed to form an aluminum oxide film layer.
[0078] Preparation Example 16: Graphene-modified polyaniline resin is made of the following raw materials in percentage by mass: 4 wt% of hydroxylated graphene, 5 wt% of nano-carbon fiber treated with low-temperature plasma, 1 wt% of spherical alumina powder with surface hydrophilic treatment, and the remainder is polyaniline resin.
[0079] The preparation method of graphene-modified polyaniline resin is as follows:
[0080] Step 1, hydroxylated graphene (TNRGOH), customized by Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences;
[0081] Low-temperature plasma treatment of nanocarbon fibers: Nano-scale carbon fibers (diameter 10-30 nm, length 10-30 microns) from Dalian Dongsen Chemical Co., Ltd. were placed in an MWP-200 low-temperature plasma treatment machine, the temperature was adjusted to 3-4°C, and low-temperature plasma treatment was performed for 5 minutes in an ozone atmosphere to obtain surface carboxyl-modified nanocarbon fibers;
[0082] The spherical alumina powder was subjected to surface hydrophilic treatment: 100 g of spherical alumina with an average particle size of 10 μm (customized by Zhejiang Yamei Nanotechnology) was dry-kneaded with 4 g of KH570 coupling agent and 1 g of KR 138S titanate coupling agent for 30 min to obtain spherical alumina powder with surface hydrophilic treatment;
[0083] Step 2, dissolving aniline in a 1.5 mol / L hydrochloric acid solution and mixing well to obtain an acidic polyaniline aqueous solution, wherein the mass ratio of aniline to hydrochloric acid in the hydrochloric acid solution is 1:9;
[0084] At the same time, the hydroxylated graphene in step 1, the spherical alumina powder with hydrophilic surface treatment, and the nano-carbon fiber treated with low-temperature plasma were added into deionized water, with a solid-liquid ratio of 1:19, and ultrasonic dispersion treatment was performed for 4 hours, with an ultrasonic frequency of 44kHz and a power of 1600W to obtain an aqueous dispersion of a high thermal conductivity powder;
[0085] Step 3, at a speed of 320 rpm / min, the aqueous dispersion of the high thermal conductivity powder is added dropwise to the acidic polyaniline aqueous solution at a dropping speed of 2 drops / s, and after the dropping is completed, the mixture is stirred at a speed of 320 rpm / min for 8 hours to obtain a milky white mixed solution;
[0086] Step 4, cooling to 0-4°C, adding 0.2 wt% initiator ammonium persulfate to the milky white mixed solution at 240 rpm / min, stirring for 12 hours, and maintaining at 0-4°C for 24 hours to allow aniline to fully polymerize to obtain a solution containing a black-green precipitate;
[0087] Step 5: The solution containing the black-green precipitate is subjected to vacuum filtration to obtain the black-green precipitate, which is washed alternately with deionized water and ethanol for 4 times, and finally vacuum dried to obtain graphene-modified polyaniline resin particles.
[0088] The difference between Preparation Example 17 and Preparation Example 16 is that the graphene-modified polyaniline resin is made of the following raw materials in percentage by mass: 6wt% of hydroxylated graphene, 6wt% of nano-carbon fiber treated with low-temperature plasma, 4wt% of spherical alumina powder with surface hydrophilic treatment, and the remainder is polyaniline resin.
[0089] The difference between Preparation Example 18 and Preparation Example 16 is that the graphene-modified polyaniline resin is made of the following raw materials in percentage by mass: 5wt% of hydroxylated graphene, 8wt% of nano-carbon fibers treated with low-temperature plasma, 3wt% of spherical alumina powder with surface hydrophilic treatment, and the remainder is polyaniline resin.
[0090] The difference between Preparation Example 19 and Preparation Example 16 is that the graphene-modified polyaniline resin is made of the following raw materials in percentage by mass: 8wt% of hydroxylated graphene, 10wt% of nano-carbon fiber treated with low-temperature plasma, 5wt% of spherical alumina powder with surface hydrophilic treatment, and the remainder is polyaniline resin.
[0091] The difference between Preparation Example 20 and Preparation Example 16 is that the graphene-modified polyaniline resin is made of the following raw materials in percentage by mass: 5wt% of hydroxylated graphene, 8wt% of nano-carbon fibers treated with low-temperature plasma, 3wt% of the surface-doped graphene-modified spherical alumina in Preparation Example 10 with surface hydrophilic treatment, and the remainder is polyaniline resin.
[0092] The difference between Preparation Example 21 and Preparation Example 16 is that the graphene-modified polyaniline resin is made of the following raw materials in percentage by mass: 4 wt % of hydroxylated graphene, 1 wt % of spherical alumina, and the remainder is polyaniline resin.
[0093] The difference between Preparation Example 22 and Preparation Example 16 is that the graphene-modified polyaniline resin is made of the following raw materials in percentage by mass: 5wt% of nano-carbon fibers treated with low-temperature plasma, 1wt% of spherical alumina, and the remainder is polyaniline resin.
[0094] Example
[0095] A graphene-modified high-thermal-conductivity plastic is made of the following raw materials in percentage by mass: 10-20% of graphene-modified polyaniline resin, 5-10wt% of surface-modified aramid fiber, 15-30% of nanometer high-thermal-conductivity insulation filler, and the balance is nylon matrix resin.
[0096] The surface-modified aramid fiber comprises aramid fiber and a high thermal conductivity metal oxide film fixedly connected to the aramid fiber, wherein the high thermal conductivity metal oxide film is made by a sol-gel method.
[0097] The nylon matrix resin is at least one of PA6, PA66, PA56, PA612, and PA1212.
[0098] The nanometer high thermal conductivity insulating filler is at least one of aluminum oxide, aluminum nitride, boron nitride and zirconium nitride.
[0099] Preferably, the nano high thermal conductive insulating filler is composed of spherical alumina, spherical aluminum nitride, and boron nitride nanosheets in a mass ratio of (3-6):(3-6):(0.5-2).
[0100] Further preferably, the nano high thermal conductive insulating filler is composed of spherical alumina, spherical aluminum nitride, and boron nitride nanosheets in a mass ratio of 5:4:1.
[0101] In order to further improve the overall thermal conductivity and ensure the overall good anti-electrical breakdown insulation safety performance, the spherical aluminum oxide is surface-doped graphene-modified spherical aluminum oxide. Specifically, the surface-doped graphene-modified spherical aluminum oxide includes spherical aluminum oxide with an average particle size of 1-40 microns and 3D graphene fixed to the spherical aluminum oxide by sintering nano-silver clusters. And the spherical aluminum nitride is surface-doped graphene-modified spherical aluminum nitride; the surface-doped graphene-modified spherical aluminum nitride includes spherical aluminum nitride with an average particle size of 1-40 microns and 3D graphene fixed to the spherical aluminum nitride by sintering nano-silver clusters.
[0102] The average particle size of the boron nitride nanosheets is 200-600 nm, preferably the boron nitride nanosheets have an average particle size of 200 nm.
[0103] The graphene-modified polyaniline resin contains 4-8wt% of hydroxylated graphene, 5-10wt% of nano-carbon fibers treated with low-temperature plasma, and 1-5wt% of spherical alumina powder with surface hydrophilic treatment.
[0104] The graphene-modified polyaniline resin contains 5-6wt% of hydroxylated graphene, 6-8wt% of nanocarbon fibers (the length of the nanocarbon fibers is 5-50um, and the diameter of the nanocarbon fibers is 150-200nm), and 3-4wt% of spherical alumina powder with a surface hydrophilic treatment. The spherical alumina powder with a surface hydrophilic treatment is obtained by surface hydrophilic treatment with a coupling agent, and the average particle size of the spherical alumina powder is 50-500nm. The coupling agent used for the surface hydrophilic modification of the spherical alumina powder is composed of γ-methacryloxypropylmethyldimethoxysilane and titanate coupling agent KR 138S in a mass ratio of (80-85):(15-20).
[0105] The preparation method of graphene-modified polyaniline resin comprises the following steps:
[0106] Step 1: Preparation of hydroxylated graphene or direct purchase of commercially available hydroxylated graphene;
[0107] At the same time, the nano-carbon fiber is treated with low-temperature plasma; the surface of the spherical alumina powder is treated with hydrophilicity;
[0108] Step 2, dissolving aniline in a 1-2 mol / L hydrochloric acid solution and mixing well to obtain an acidic polyaniline aqueous solution, wherein the mass ratio of aniline to hydrochloric acid is 1:(8-10);
[0109] At the same time, the hydroxylated graphene in step 1, the spherical alumina powder with hydrophilic surface treatment, and the nano-carbon fiber treated with low-temperature plasma are added into deionized water, with a solid-liquid ratio of 1:(19-24), and ultrasonically dispersed for 3-6 hours to obtain an aqueous dispersion of a high thermal conductivity powder;
[0110] Step 3, at a speed of 300-500 rpm / min, the aqueous dispersion of the high thermal conductivity powder is added dropwise to the acidic polyaniline aqueous solution at a dropping speed of 1-2 drops / s, and after the dropping is completed, the mixture is stirred at a speed of 300-500 rpm / min for 6-8 hours to obtain a milky white mixed solution;
[0111] Step 4, cooling to 0-4°C, adding 0.1-0.5 wt% of initiator to the milky white mixed solution at 160-240 rpm / min, stirring for 10-12 hours, and standing at 0-4°C for 20-24 hours to allow aniline to fully polymerize to obtain a solution containing a black-green precipitate;
[0112] Step 5: The solution containing the black-green precipitate is subjected to vacuum filtration to obtain the black-green precipitate, which is then washed alternately with deionized water and ethanol for at least three times, and finally vacuum dried to obtain graphene-modified polyaniline resin particles.
[0113] The preferred formula is that the graphene-modified high thermal conductivity plastic is made of the following raw materials in mass percentage: 15-18% graphene-modified polyaniline resin, 6-8wt% surface-modified aramid fiber, 24-28% nanometer high thermal conductivity insulation filler, and the balance is nylon matrix resin. The nylon matrix resin is composed of PA66 and PA612 in a mass ratio of (6-8): (2-4).
[0114] The preparation method of graphene-modified high thermal conductivity plastic comprises the following steps:
[0115] Step 1. Preparation of graphene-modified polyaniline resin and surface-modified aramid fiber; simultaneously, surface treatment of nano-high thermal conductive insulating filler is performed, and nano-high thermal conductive insulating filler and coupling agent are dry-kneaded at a mass ratio of 100:(3-8) for at least 0.5h;
[0116] Step 2. The nylon matrix resin is dissolved in an organic solvent to form a nylon solution, the mass of the organic solvent is 8-12 times the mass of the nylon matrix resin, and the graphene-modified polyaniline resin, the surface-modified aramid fiber, and the surface-treated nano-high thermal conductive insulating filler in step 1 are added to the nylon solution. After fully dissolved, the mixture is stirred at 200-400 rpm / min for 10-15 min, ultrasonically dispersed for 2-4 h, and the organic solvent is removed by vacuum distillation to obtain a solid mixed resin;
[0117] Step 3. The solid mixed resin in step 3 is crushed and vacuum dried to obtain a mixed resin powder;
[0118] Step 4. Extrude, granulate and dry the mixed resin powder in step 3 to obtain a high thermal conductivity and high insulation plastic masterbatch;
[0119] Step 5. Using the high thermal conductivity and high insulation plastic masterbatch in step 4 for extrusion, melting, and injection molding to obtain a semi-finished plastic;
[0120] Step 6. Heat treat the semi-finished plastic in step 5, raise the temperature to 60-65°C at 0.5-3°C / min and keep it for 10-30min, then raise the temperature to 90-125°C at 2-4°C / min and keep it for 30-45min, lower the temperature to 40-45°C at 0.2-0.8°C / min, open the furnace and cool naturally to room temperature to obtain the finished graphene modified high thermal conductivity plastic.
[0121] Example 1: A graphene-modified high thermal conductivity plastic is made of the following raw materials in percentage by mass: 10% of the graphene-modified polyaniline resin in Preparation Example 16, 5wt% of the surface-modified aramid fiber in Preparation Example 12, 15% of the nano high thermal conductivity insulating filler in Preparation Example 1, and the remainder is nylon matrix resin PA66 (DuPont 101 powder, USA).
[0122] A method for preparing a graphene-modified high thermal conductivity plastic comprises the following steps:
[0123] Step 1. Preparation of graphene-modified polyaniline resin, see Preparation Example 16;
[0124] The preparation of surface-modified aramid fibers is described in Preparation Example 12;
[0125] The preparation of the nanometer high thermal conductivity insulating filler with surface hydrophilic treatment is shown in Preparation Example 1;
[0126] Step 2. The nylon matrix resin PA66 is dissolved in N,N-dimethylformamide to form a nylon solution, the mass of N,N-dimethylformamide is 9 times the mass of the nylon matrix resin PA66, and the graphene-modified polyaniline resin of Preparation Example 16 in Step 1, the surface-modified aramid fiber in Preparation Example 12, and the surface-hydrophilic nano-high thermal conductive insulating filler in Preparation Example 1 are added to the nylon solution. After fully dissolved, the mixture is stirred at 240 rpm / min for 15 min, ultrasonically dispersed for 3 h, with an ultrasonic frequency of 75 kHz and an ultrasonic power of 1200 W, and N,N-dimethylformamide is removed by vacuum distillation to obtain a solid mixed resin;
[0127] Step 3. The solid mixed resin in step 3 is crushed to obtain a mixed resin powder with a particle size of 0.1-0.3 mm, and then vacuum dried for 2 h to obtain a product mixed resin powder with a particle size of 0.1-0.3 mm;
[0128] Step 4. The mixed resin powder in step 3 is placed in a twin-screw extruder for extrusion melting, wire drawing, water cooling, granulation, and drying. The extrusion temperature is 28-295°C, the die temperature is 290°C, the drying temperature is 80°C, and the drying time is 6h to obtain a high thermal conductivity and high insulation plastic masterbatch with a particle size of 0.4-0.6mm and a water content of less than 0.2%;
[0129] Step 5. The high thermal conductivity and high insulation plastic masterbatch in step 4 is placed in a twin-screw extruder for extrusion melting and injection molding, the extrusion temperature is 285-295°C, the die temperature is 290°C, the injection pressure is 80MPa, the injection speed is 50mm / s, and the injection mold temperature is 85°C to obtain a semi-finished plastic;
[0130] Step 6. Heat treat the semi-finished plastic in step 5, raise the temperature to 60°C at 1°C / min and keep it for 15 minutes, then raise the temperature to 105°C at 3°C / min and keep it for 45 minutes, then cool it to 45°C at 0.5°C / min, open the furnace and cool it naturally to room temperature to obtain the finished graphene-modified high thermal conductivity plastic.
[0131] The difference between Example 2 and Example 1 is that a graphene-modified high thermal conductivity plastic is made of the following raw materials in percentage by mass: 15% of the graphene-modified polyaniline resin in Preparation Example 16, 8wt% of the surface-modified aramid fiber in Preparation Example 12, 25% of the nano high thermal conductivity insulating filler in Preparation Example 1, and the remainder is nylon matrix resin PA66.
[0132] The difference between Example 3 and Example 1 is that a graphene-modified high thermal conductivity plastic is made of the following raw materials in percentage by mass: 20% of the graphene-modified polyaniline resin in Preparation Example 16, 10wt% of the surface-modified aramid fiber in Preparation Example 12, 30% of the nano high thermal conductivity insulating filler in Preparation Example 1, and the remainder is nylon matrix resin PA66.
[0133] The difference between Example 4 and Example 1 is that a graphene-modified high thermal conductivity plastic is made of the following raw materials in percentage by mass: 15% of the graphene-modified polyaniline resin in Preparation Example 16, 8wt% of the surface-modified aramid fiber in Preparation Example 12, 25% of the nanometer high thermal conductivity insulating filler in Preparation Example 1, and the balance is nylon matrix resin. The nylon matrix resin is composed of PA66 and PA612 (DuPont 151L) in a mass ratio of 7:3.
[0134] The difference between Example 5 and Example 2 is that the nanometer high thermal conductivity insulating filler in Preparation Example 1 is replaced by the nanometer high thermal conductivity insulating filler in Preparation Example 2.
[0135] The difference between Example 6 and Example 2 is that the nanometer high thermal conductivity insulating filler in Preparation Example 1 is replaced by the nanometer high thermal conductivity insulating filler in Preparation Example 3.
[0136] The difference between Example 7 and Example 2 is that the nanometer high thermal conductivity insulating filler in Preparation Example 1 is replaced by the nanometer high thermal conductivity insulating filler in Preparation Example 4.
[0137] The difference between Example 8 and Example 2 is that the nanometer high thermal conductivity insulating filler in Preparation Example 1 is replaced by the nanometer high thermal conductivity insulating filler in Preparation Example 5.
[0138] The difference between Example 9 and Example 2 is that the nanometer high thermal conductivity insulating filler in Preparation Example 1 is replaced by the nanometer high thermal conductivity insulating filler in Preparation Example 6.
[0139] The difference between Example 10 and Example 2 is that the nanometer high thermal conductivity insulating filler in Preparation Example 1 is replaced by the nanometer high thermal conductivity insulating filler in Preparation Example 7.
[0140] The difference between Example 11 and Example 2 is that the nanometer high thermal conductivity insulating filler in Preparation Example 1 is replaced by the nanometer high thermal conductivity insulating filler in Preparation Example 8.
[0141] The difference between Example 12 and Example 2 is that the nanometer high thermal conductivity insulating filler in Preparation Example 1 is replaced by the nanometer high thermal conductivity insulating filler in Preparation Example 9.
[0142] The difference between Example 13 and Example 2 is that the nanometer high thermal conductivity insulating filler in Preparation Example 1 is replaced by the nanometer high thermal conductivity insulating filler in Preparation Example 10.
[0143] The difference between Example 14 and Example 2 is that the nanometer high thermal conductive insulating filler in Preparation Example 1 is replaced by the nanometer high thermal conductive insulating filler in Preparation Example 11.
[0144] The difference between Example 15 and Example 2 is that the surface-modified aramid fiber in Preparation Example 12 is replaced by the surface-modified aramid fiber in Preparation Example 13.
[0145] The difference between Example 16 and Example 2 is that the surface-modified aramid fiber in Preparation Example 12 is replaced by the surface-modified aramid fiber in Preparation Example 14.
[0146] The difference between Example 17 and Example 2 is that the surface-modified aramid fiber in Preparation Example 12 is replaced by the surface-modified aramid fiber in Preparation Example 15.
[0147] The difference between Example 18 and Example 2 is that the graphene-modified polyaniline resin in Preparation Example 16 is replaced by the graphene-modified polyaniline resin in Preparation Example 17.
[0148] The difference between Example 19 and Example 2 is that the graphene-modified polyaniline resin in Preparation Example 16 is replaced by the graphene-modified polyaniline resin in Preparation Example 18.
[0149] The difference between Example 20 and Example 2 is that the graphene-modified polyaniline resin in Preparation Example 16 is replaced by the graphene-modified polyaniline resin in Preparation Example 19.
[0150] The difference between Example 21 and Example 2 is that the graphene-modified polyaniline resin in Preparation Example 16 is replaced by the graphene-modified polyaniline resin in Preparation Example 20.
[0151] The difference between Example 22 and Example 2 is that a graphene-modified high thermal conductivity plastic is made of the following raw materials in percentage by mass: 15% of the graphene-modified polyaniline resin in Preparation Example 20, 8wt% of the surface-modified aramid fiber in Preparation Example 14, 25% of the nanometer high thermal conductivity insulating filler in Preparation Example 11, and the balance is nylon matrix resin. The nylon matrix resin is composed of PA66 and PA612 (DuPont 151L) in a mass ratio of 7:3.
[0152] Comparative Example
[0153] The difference between Comparative Example 1 and Example 1 is that a graphene-modified high thermal conductivity plastic is made of the following raw materials in percentage by mass: 8% of the graphene-modified polyaniline resin in Preparation Example 16, 2wt% of the surface-modified aramid fiber in Preparation Example 12, 10% of the nano high thermal conductivity insulating filler in Preparation Example 1, and the remainder is nylon matrix resin PA66.
[0154] The difference between Comparative Example 2 and Example 1 is that a graphene-modified high thermal conductivity plastic is made of the following raw materials in percentage by mass: 22% of the graphene-modified polyaniline resin in Preparation Example 16, 12wt% of the surface-modified aramid fiber in Preparation Example 12, 32% of the nano high thermal conductivity insulating filler in Preparation Example 1, and the remainder is nylon matrix resin PA66.
[0155] The difference between Comparative Example 3 and Example 1 is that a graphene-modified high thermal conductivity plastic is made of the following raw materials in percentage by mass: 5wt% of the surface-modified aramid fiber in Preparation Example 12, 15% of the nano high thermal conductivity insulating filler in Preparation Example 1, and the remainder is nylon matrix resin PA66.
[0156] The difference between Comparative Example 4 and Example 1 is that a graphene-modified high thermal conductivity plastic is made of the following raw materials in percentage by mass: 10% of the graphene-modified polyaniline resin in Preparation Example 16, 15% of the nano high thermal conductivity insulating filler in Preparation Example 1, and the balance is nylon matrix resin PA66.
[0157] The difference between Comparative Example 5 and Example 1 is that a graphene-modified high thermal conductivity plastic is made of the following raw materials in percentage by mass: 10% of the graphene-modified polyaniline resin in Preparation Example 16, 5wt% of the surface-modified aramid fiber in Preparation Example 12, and the remainder is nylon matrix resin PA66.
[0158] The difference between Comparative Example 6 and Example 1 is that a graphene-modified high thermal conductivity plastic is made of the following raw materials in mass percentage: 40% of spherical alumina with an average particle size of 10 microns and the remainder of nylon matrix resin PA66. 140 g of spherical alumina with an average particle size of 10 microns is dry-kneaded with 9 g of KH570 coupling agent and 1 g of KR 138S titanate coupling agent for 30 minutes to obtain spherical alumina with hydrophilic surface modification.
[0159] The difference between Comparative Example 7 and Example 2 is that the surface-modified aramid fiber in Preparation Example 12 is replaced by 4 mm long aramid F-12 monofilament.
[0160] The difference between Comparative Example 8 and Example 2 is that the graphene-modified polyaniline resin in Preparation Example 16 is replaced by the graphene-modified polyaniline resin in Preparation Example 21.
[0161] The difference between Comparative Example 9 and Example 2 is that the graphene-modified polyaniline resin in Preparation Example 16 is replaced by the graphene-modified polyaniline resin in Preparation Example 22.
[0162] The difference between Comparative Example 10 and Example 2 is that the graphene-modified polyaniline resin in Preparation Example 16 is replaced by polyaniline resin. The preparation method of polyaniline resin is as follows: aniline is dissolved in a 1.5 mol / L hydrochloric acid solution and mixed to obtain an acidic polyaniline aqueous solution, wherein the mass ratio of aniline to the hydrochloric acid in the hydrochloric acid solution is 1:9; then the temperature is lowered to 0-4°C, 0.2 wt% of initiator ammonium persulfate is added to the milky white mixed solution at 240 rpm / min, stirred for 12 hours, maintained at 0-4°C and allowed to stand for 24 hours to allow aniline to fully polymerize to obtain a solution of a light green precipitate; then the precipitate is subjected to reduced pressure filtration to obtain a black-green precipitate, which is washed alternately with deionized water and ethanol 4 times, and finally vacuum dried to obtain polyaniline resin particles.
[0163] Performance test: 1. Thermal conductivity is measured according to ASTM D 5470-06 Standard Test Method for Thermal Transfer Performance of Thermally Conductive Electrical Insulating Materials. 2. Dielectric breakdown strength is measured according to GB1408.1-2006 "Electrical Strength Test Method for Insulating Materials". 3. Flame retardant performance test method: measured according to the US UL94 fire protection standard. 4. Flexural strength is measured according to ASTM D790-03 Standard Test Method for Flexural Performance of Unreinforced and Reinforced Plastics and Electrical Insulating Materials.
[0164] Table 1 is a table of test parameters of graphene-modified high thermal conductivity plastics in Examples 1-22 and Comparative Examples 1-10
[0165]
[0166]
[0167] Combining Examples 1-4 and Comparative Examples 1-6 with Table 1, it can be seen that the graphene-modified high thermal conductivity plastic is made of the following raw materials in percentage by mass: 10-20% graphene-modified polyaniline resin, 5-10wt% surface-modified aramid fiber, 15-30% nano high thermal conductivity insulating filler, and the balance is nylon matrix resin. The prepared graphene-modified high thermal conductivity plastic has excellent comprehensive performance.
[0168] It can be seen from Example 2 and Comparative Example 7 and Table 1 that the surface-modified aramid fiber can effectively conduct the heat conduction channel of the three-dimensional network structure, which is beneficial to improving the thermal conductivity and bending strength of the graphene-modified high thermal conductivity plastic.
[0169] It can be seen from Example 2, Examples 18-21 and Comparative Examples 8-10 and Table 1 that the graphene-modified polyaniline resin prepared by Preparation Examples 16-20 in the present application can improve the thermal conductivity, bending strength and flame retardancy of the graphene-modified high thermal conductivity plastic while ensuring that the graphene-modified high thermal conductivity plastic has good electrical breakdown resistance and insulation performance.
[0170] It can be seen from Example 2 and Example 5-14 and Table 1 that the nano-high thermal conductivity insulating filler composed of spherical alumina, spherical aluminum nitride and boron nitride nanosheets in a mass ratio of (3-6):(3-6):(0.5-2) has relatively good comprehensive performance of the graphene-modified high thermal conductivity plastic, and the nano-high thermal conductivity insulating filler composed of spherical alumina, spherical aluminum nitride and boron nitride nanosheets in a mass ratio of 5:4:1 is suitable for the industrial production of graphene-modified high thermal conductivity plastics and has the best economic cost performance.
[0171] Combining Example 2 and Examples 15-17 with Table 1, it can be seen that the surface-modified aramid fibers produced under different preparation processes will affect the thermal conductivity and bending strength of the graphene-modified high thermal conductivity plastic. Based on the formulation of this application, the performance of the graphene-modified high thermal conductivity plastic prepared by the surface-modified aramid fibers in Preparation Example 12 is relatively good.
[0172] Combining Example 2 and Examples 18-22 with Table 1, it can be seen that the graphene-modified polyaniline resin produced under different preparation processes has some influence on the thermal conductivity and bending strength of the graphene-modified high thermal conductivity plastic. Based on the formulation of this application, Example 22 is the best comprehensive performance solution for the graphene-modified high thermal conductivity plastic.
[0173] In summary, the high thermal conductivity plastic prepared in this application not only has good thermal conductivity and heat dissipation, but also has good mechanical properties, flame retardancy and anti-electrical breakdown insulation safety, and is suitable for the field of shell materials for thermal runaway protection of power batteries.
[0174] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A graphene-modified high thermal conductivity plastic, characterized in that: The high thermal conductivity plastic is mainly prepared from nylon matrix resin, graphene-modified polyaniline resin, surface-modified aramid fiber, and nanometer high thermal conductivity insulating filler; The mass of the surface-modified aramid fiber accounts for 5-10% of the total mass of the high thermal conductivity plastic; The surface-modified aramid fiber comprises an aramid fiber and a high thermal conductivity metal oxide film fixedly connected to the aramid fiber; The nanometer high thermal conductivity insulating filler is at least one of aluminum oxide, aluminum nitride, boron nitride and zirconium nitride; The mass of the nano high thermal conductivity insulating filler accounts for 15-30% of the total mass of the high thermal conductivity plastic; The mass of the graphene-modified polyaniline resin accounts for 10-20% of the total mass of the high thermal conductivity plastic; The graphene-modified polyaniline resin contains 4-8wt% of hydroxylated graphene, 5-10wt% of nano-carbon fiber, and 1-5wt% of spherical alumina powder with hydrophilic surface treatment; the nano-carbon fiber is treated with low-temperature plasma; The nylon matrix resin is at least one of PA6, PA66, PA56, PA612, and PA1212.
2. The graphene-modified high thermal conductivity plastic according to claim 1, characterized in that: The length of the aramid fiber is 0.5-5.0 mm; an aluminum oxide film layer is formed on the surface of the aramid fiber by a sol-gel method.
3. The graphene-modified high thermal conductivity plastic according to claim 1, characterized in that: The nanometer high thermal conductivity insulating filler is composed of spherical aluminum oxide, spherical aluminum nitride and boron nitride nanosheets in a mass ratio of (3-6):(3-6):(0.5-2).
4. The graphene-modified high thermal conductivity plastic according to claim 3, characterized in that: The nanometer high thermal conductivity insulating filler is composed of spherical aluminum oxide, spherical aluminum nitride and boron nitride nanosheets in a mass ratio of 5:4:
1.
5. A graphene-modified high thermal conductivity plastic according to claim 3 or 4, characterized in that: The spherical alumina is surface-doped graphene-modified spherical alumina; the surface-doped graphene-modified spherical alumina comprises spherical alumina with an average particle size of 1-40 microns and 3D graphene fixed to the spherical alumina by sintering of nanosilver clusters; the average particle size of the boron nitride nanosheets is 200-600nm.
6. A graphene-modified high thermal conductivity plastic according to claim 3 or 4, characterized in that: The spherical aluminum nitride is surface-doped graphene-modified spherical aluminum nitride; the surface-doped graphene-modified spherical aluminum nitride comprises spherical aluminum nitride with an average particle size of 1-40 microns and 3D graphene fixed to the spherical aluminum nitride by sintering of nano-silver clusters.
7. The graphene-modified high thermal conductivity plastic according to claim 3, characterized in that: The mass of the surface-modified aramid fiber accounts for 6-8% of the total mass of the high thermal conductivity plastic; the mass of the nano high thermal conductivity insulating filler accounts for 24-28% of the total mass of the high thermal conductivity plastic; the mass of the graphene-modified polyaniline resin accounts for 15-18% of the total mass of the high thermal conductivity plastic; the nylon matrix resin is composed of PA66 and PA612 in a mass ratio of (6-8):(2-4).
8. The graphene-modified high thermal conductivity plastic according to claim 7, characterized in that: The graphene-modified polyaniline resin contains 5-6wt% of hydroxylated graphene, 6-8wt% of nano-carbon fibers, and 3-4wt% of spherical alumina powder with a surface hydrophilic treatment; the length of the nano-carbon fibers is 5-50um, and the diameter of the nano-carbon fibers is 150-200nm; the spherical alumina powder with a surface hydrophilic treatment is obtained by surface hydrophilic treatment with a coupling agent, and the average particle size of the spherical alumina powder is 50-500nm; the coupling agent used for the surface hydrophilic modification of the spherical alumina powder is composed of γ-methacryloxypropylmethyldimethoxysilane and titanate coupling agent KR138S in a mass ratio of (80-85):(15-20).
9. The graphene-modified high thermal conductivity plastic according to claim 8, characterized in that: The preparation method of the graphene-modified polyaniline resin is as follows: Step 1, preparation of hydroxylated graphene; low-temperature plasma treatment of nano-carbon fibers; surface hydrophilic treatment of spherical alumina powder; step 2, dissolving aniline in 1-2 mol / L hydrochloric acid solution and mixing to obtain an acidic polyaniline aqueous solution, wherein the mass ratio of the aniline to the hydrochloric acid is 1:(8-10); at the same time, the hydroxylated graphene in step 1, the surface hydrophilic spherical alumina powder, and the nano-carbon fibers treated with low-temperature plasma are added to deionized water, with a solid-liquid ratio of 1:(19-24), and ultrasonically dispersed for 3-6 hours to obtain an aqueous dispersion of high thermal conductivity powder; Step 3, at a speed of 300-500 rpm / min, the aqueous dispersion of the high thermal conductivity powder is added dropwise to the acidic polyaniline aqueous solution at a dropping speed of 1-2 drops / s, and after the addition is completed, stirring is continued at a speed of 300-500 rpm / min for 6-8 hours to obtain a milky white mixed solution; Step 4, cooling to 0-4°C, adding 0.1-0.5 wt% of initiator to the milky white mixed solution at 160-240 rpm / min, stirring for 10-12 hours, and standing at 0-4°C for 20-24 hours to allow aniline to fully polymerize to obtain a solution containing a black-green precipitate; Step 5: The solution containing the black-green precipitate is subjected to vacuum filtration to obtain the black-green precipitate, and the black-green precipitate is washed alternately with deionized water and ethanol for at least three times, and finally vacuum dried to obtain graphene-modified polyaniline resin particles.
10. A method for preparing the graphene-modified high thermal conductivity plastic according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1. Preparation of graphene-modified polyaniline resin and surface-modified aramid fiber; simultaneously, surface treatment of nano-high thermal conductive insulating filler is performed, and nano-high thermal conductive insulating filler and coupling agent are dry-kneaded at a mass ratio of 100:(3-8) for at least 0.5h; Step 2. The nylon matrix resin is dissolved in an organic solvent to form a nylon solution, wherein the mass of the organic solvent is 8-12 times the mass of the nylon matrix resin, and the graphene-modified polyaniline resin, the surface-modified aramid fiber, and the surface-treated nano-high thermal conductive insulating filler in step 1 are added to the nylon solution. After being fully dissolved, the mixture is stirred at 200-400 rpm / min for 10-15 min, ultrasonically dispersed for 2-4 h, and the organic solvent is removed by distillation under reduced pressure to obtain a solid mixed resin; Step 3. The solid mixed resin in step 3 is crushed and vacuum dried to obtain a mixed resin powder; Step 4. Extrude, granulate and dry the mixed resin powder in step 3 to obtain a high thermal conductivity and high insulation plastic masterbatch; Step 5. Using the high thermal conductivity and high insulation plastic masterbatch in step 4 for extrusion, melting, and injection molding to obtain a semi-finished plastic; Step 6. Heat treat the semi-finished plastic in step 5, raise the temperature to 60-65°C at 0.5-3°C / min and keep it for 10-30min, then raise the temperature to 90-125°C at 2-4°C / min and keep it for 30-45min, lower the temperature to 40-45°C at 0.2-0.8°C / min, open the furnace and cool naturally to room temperature to obtain the finished graphene modified high thermal conductivity plastic.
Citation Information
Patent Citations
High temperature resistant enhanced thermoplastic composite material and preparation method thereof
CN107459816A
Polyaniline / aramid nanofiber conductive composite film and preparation method thereof
CN110628215A
Cited By
High-heat-dissipation LED car lamp
CN224580152U